Deception and confession: Experimental evidence from a deception game in Japan - Keiko Aoki; Kenju Akai; Kenta Onoshiro (Osaka University, Institute of Social and Economic Research (ISER), 2010)
This study investigated lying behavior and the behavior of people who are deceived by using a deception game (Gneezy, 2005) in both anonymity and face-to-face treatments. Subjects consist of students and non-students (citizens) to investigate whether lying behavior is depended on socioeconomic backgrounds. To explore how liars feel about lying, we give senders a chance to confess their behaviors to their counter partner for the guilty aversion of lying. The following results are obtained: i) a frequency of lying behavior for students is significantly higher than that for non-students at a payoff in the anonymity treatment, but that is not significantly difference between the anonymity and face-to-face treatments; ii) lying behavior is not influenced by gender; iii) a frequency of confession is higher in the face-to-face treatment than in the anonymity treatment; and iv) the receivers who are deceived are more likely to believe a sender's message to be true in the anonymity treatment. This study implies that the existence of the partner prompts liars to confess their behavior because they may feel remorse or guilt.
Keywords: 330; deception game; lying behavior; experiment; face-to-face; anonymity; confession; Spieltheorie; Ethik; Soziale Kontrolle; Soziales Verhalten; Theorie